Perceived Value Dimensions and Guest Satisfaction: An Analysis of Functional, Social and Emotional Values in Five-Star Hotel Organizations - Mohd Kamal, Malina Hanum; Shattar, Noristisarah Abd; Azhar, Farisya Idayu; Tuan Ahmad Jafri, Tuan Sharifah Irene Natasha; Kamal, Ema Maliha Mohd (Information Management and Business Review, 2025)
Customer satisfaction is one of the most essential measurements that indicates how well a company’s goods or services live up to the expectations of its clients. In the hotel industry, the level of customer satisfaction is represented by guest satisfaction. This study aims to explore factors that influence guest satisfaction in hotel organizations. Specifically, the study aims to examine the influence of perceived value dimensions, which are functional value, social value, and emotional value, on hotel guests’ satisfaction. A quantitative study approach has been adopted through online survey questionnaires involving 370 respondents who have prior experience staying in five-star hotel organizations. Data have been gathered and analyzed using a reliability test, descriptive statistics, correlation, and multiple regression analyses with the assistance of the IBM SPSS software. The data have indicated that the perceived value dimensions have a significant effect on the hotel guests’ satisfaction. The findings have revealed that social value and emotional value positively influence the hotel guests’ satisfaction with social value being the most significant factor. These results underscore the importance of the perceived value dimensions as the measurement of the hotel guests’ satisfaction. The study contributes to the limited number of studies that focus on the trend and antecedents of customer satisfaction in the hotel industry. Besides, it also serves as a foundation, inspiring future researchers to explore more on other factors that may shape guest satisfaction and how it contributes towards customer retention in hotel organizations.